2017
DOI: 10.1016/j.seppur.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction fractionation of Li-ion battery leachate containing Li, Ni, and Co

Abstract: In this research, the separation of Li, Ni, and Co by solvent extraction was studied from synthetic Li-ion battery waste leachate. The purpose was to propose a process for producing all the metals with over 99.5% purities, as the purity demands for battery grade metals are high. Emphasis was also placed on obtaining pure Li raffinate in the early stage of the process, as societal interest in Li is growing rapidly. Thus, the purpose was to first extract Co and Ni selectively yielding pure Li raffinate, and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 22 publications
1
38
0
1
Order By: Relevance
“…(Lv et al, 2018). The metal ion concentrations used in our case are lower than the one encountered in the real leach liquor, in order to simplify the experiment (Virolainen et al, 2017).…”
Section: Solvent Extractionmentioning
confidence: 99%
“…(Lv et al, 2018). The metal ion concentrations used in our case are lower than the one encountered in the real leach liquor, in order to simplify the experiment (Virolainen et al, 2017).…”
Section: Solvent Extractionmentioning
confidence: 99%
“…1.0 mM cobalt chloride, nickel chloride, and lithium chloride were dissolved in ion-exchanged water to prepare an aqueous solution as a model leaching solution from a waste lithium ion battery. The solution was separated from each other according to the process (Virolainen et al, 2017) shown in Figure 1. Cobalt and nickel were transferred to the oil phase and lithium was separated and recovered by the extraction step 1 (Loading).…”
Section: Methodsmentioning
confidence: 99%
“…After the leaching step, a complex mixture containing the metal ions in aqueous acidic solution is obtained. This solution contains mainly lithium, cobalt and nickel ions at various concentrations [14]. These metals have to be separated and recovered.…”
Section: Introductionmentioning
confidence: 99%